Recovery of the Total Birth Brachial Plexus Palsy without Surgical Treatment: A Single-Center, Retrospective Study and Literature Review - Vinitpairot, Chaiyos; Jianmongkol, Surut (Archives of Plastic Surgery, 2024)
Background Spontaneous recovery of a birth brachial plexus disorder is difficult to predict. Although root avulsion and total plexus injury is indicated for surgical management, early nerve surgery is still doubtful. Hand motion is obviously an important indicator for predicting the function of an affected limb. However, the timing for diagnosing a transient or true total plexus injury from hand recovery is controversial. This study aimed to report the recovery time of total birth brachial plexus palsy in patients who did not undergo surgery due to various reasons.Methods In this 15-year retrospective chart review, 45 patients of total birth brachial plexus injury with a mean follow-up time of 34.5 months, were included. Although patients met surgical indications, surgical management was abandoned for a variety of reasons. Imaging was not performed routinely and, nerve conduction study and Horner's syndrome were not consistently recorded in the past. All patients were evaluated for clinical improvement by motor power grading. The recovery time was reported as the median and interquartile range.Results Forty-five patients were diagnosed with total birth brachial plexus injury. Out of 45 patients, 36 showed clinical evidence of recovering their hand motion within a median of 3 months. The median time for the recovery of elbow flexion and shoulder abduction was 4 months. The median for achieving antigravity or full motion recovery of elbow flexion, shoulder abduction, and hand flexion were 10, 10.5, and 7 months, respectively.Conclusion In this study, spontaneous recovery of shoulder, elbow and hand motion substantially occurred in the patient diagnosed with a total birth brachial plexus palsy. True total plexus palsy can be distinguished from transient palsy by the recovery of hand motion at 3 months. Most of the patients, who had spontaneous recovery, potentially achieved antigravity or full hand movement without surgery.
Keywords: birth brachial plexus palsy; spontaneous recovery; global palsy; natural history